Redefining Zone II: Anatomy of the Flexor Digitorum Superficialis Insertion. (May 2019) - Nicholson, Luke T.; Hill, Jeffrey R.; McKnight, Braden; Heckmann, Nathanael; Stevanovic, Milan; Ghiassi, Alidad
Background: Flexor zone II is defined as the region spanning the proximal aspect of the A1 pulley to the insertion of the flexor digitorum superficialis (FDS) tendon. Descriptions of the FDS insertion are inconsistent in the literature, but zones of injury are frequently determined with reference to superficial landmarks. The purpose of this study was to describe the footprint of the FDS insertion and define its relationship to the proximal interphalangeal (PIP) skin crease.Methods: The FDS insertion on the index, middle, ring, and small fingers was dissected in 6 matched pairs of fresh-frozen cadaveric hands. A Kirschner wire was used to mark the level of the PIP skin crease on bone before measurements of the FDS footprint and its position relative to the PIP skin crease were made using digital calipers.Results: The radial and ulnar FDS slips inserted a mean distance of 3.22 mm from the distal aspect of the PIP skin crease and varied by digit. The mean distal extent of the FDS insertion was 8.29 mm. The mean length of the insertion of each FDS slip was 5.15 mm and the mean width was 1.9 mm.Conclusions: The radial and ulnar FDS slips insert on average 3.22 mm distal to the PIP skin crease and vary by digit. Knowledge of the FDS insertion is clinically relevant when differentiating between flexor zone I and zone II injuries, planning surgical approaches to the finger, and in guiding patient expectations for surgery given the variability in outcome based on zone of injury.